2021
DOI: 10.3390/medicina57050474
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, a Dimension of Impaired Functional Status in Advanced COPD: Utility and Clinical Applicability

Abstract: Background and Objectives: In advanced chronic obstructive pulmonary disease (COPD), functional status is significantly impaired mainly as a result of disease related respiratory symptoms such as dyspnea or as a result of fatigue, which is the extra-respiratory symptom the most prevalent in this setting. “Physical” frailty, considered to be an aging phenotype, has defining traits that can also be considered when studying impaired functional status, but little is known about this relationship in advanced COPD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Moreover, a causal relationship could not be established, since we could not control for all possible factors explaining this improvement. For instance, it was not possible to study in detail the physical activity levels, type of comorbidities, and medication, which might have potential effects in functional status [ 4 , 48 ]. Therefore, more research is needed to corroborate our findings and establish an adequate frequency for clinical monitoring of people with COPD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a causal relationship could not be established, since we could not control for all possible factors explaining this improvement. For instance, it was not possible to study in detail the physical activity levels, type of comorbidities, and medication, which might have potential effects in functional status [ 4 , 48 ]. Therefore, more research is needed to corroborate our findings and establish an adequate frequency for clinical monitoring of people with COPD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional status is an important and meaningful outcome in people with COPD [ 3 ]. It refers to the ability to provide for life’s necessities, i.e., activities that people do during their lives to meet basic needs, fulfil usual roles, and maintain their health and wellbeing [ 4 , 5 ]. Prior evidence has shown that poor functional status is a predictor of acute exacerbations, hospital admissions, and increased mortality in people with COPD [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frailty poses a possible three-fold increase in mortality in lung diseases [5 ▪ ,6–8]. Incident frailty is high across ILDs and influences time to mortality [5 ▪ ,9,10 ▪▪ ,11 ▪▪ ,12 ▪▪ ,13,14,15,16,17 ▪ ] and transplant success [9,10 ▪▪ ].…”
Section: Frailty and Health Related Quality Of Lifementioning
confidence: 99%
“…The characteristic frailty symptoms of weariness, lethargy, and decreased activity are more prevalent in COPD patients, and this decline in function is brought on by a reduction in muscle mass and muscle oxidative capacity, in which GDF plays a crucial regulatory role (32). The systemic characteristics of COPD, such as increased inflammatory signaling, oxidative stress, and hypoxia, can all cause an increase in the expression of GDF15, which is a stress-responsive growth regulator (33).…”
Section: The Gdf's Regulatory Impactmentioning
confidence: 99%